2022
DOI: 10.1038/s41467-022-28419-0
|View full text |Cite
|
Sign up to set email alerts
|

Mark-release-recapture experiment in Burkina Faso demonstrates reduced fitness and dispersal of genetically-modified sterile malaria mosquitoes

Abstract: Every year, malaria kills approximately 405,000 people in Sub-Saharan Africa, most of them children under the age of five years. In many countries, progress in malaria control has been threatened by the rapid spread of resistance to antimalarial drugs and insecticides. Novel genetic mosquito control approaches could play an important role in future integrated malaria control strategies. In July 2019, the Target Malaria consortium proceeded with the first release of hemizygous genetically-modified (GM) sterile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…The process of mate and reproduction are takes place before the survival rates take effect. Our mosquito density and migration is broadly consistent with previous field studies and models 20, 32 and perhaps represents an approximately 3.3 x 3.3 km area for Anopheles gambiae , though this would likely be reduced for other mosquitoes such as Aedes aegypti that have lower migration rates.…”
Section: Methodssupporting
confidence: 87%
“…The process of mate and reproduction are takes place before the survival rates take effect. Our mosquito density and migration is broadly consistent with previous field studies and models 20, 32 and perhaps represents an approximately 3.3 x 3.3 km area for Anopheles gambiae , though this would likely be reduced for other mosquitoes such as Aedes aegypti that have lower migration rates.…”
Section: Methodssupporting
confidence: 87%
“…Comparing our default dispersal rate of 0.307 to a recent study that found a mean dispersal of 171 m over 20 days 23 , we can potentially state that our mean dispersal corresponds to 101 m per week and that our simulation area length is therefore 3.3 km. A population density of 430 mosquitoes per hectare would thus yield a total population of 470,000 adults, compared to our default of 40,000 (of which 25,000 are females).…”
Section: Reproducing Females Have a Fecundity Of 𝑤′mentioning
confidence: 75%
“…The shape of the curve was chosen based on survival curves in laboratory studies 29 and to allow simulation of age-based health. The measured male survival rate in the field was measured as approximately 30% per week in one recent study 23 , and often higher in females and closer to 50% in males for older studies 30,31 . This is somewhat lower, but broadly similar to our model, considering high variation in field conditions and our need to simulate a high effective population size with limited computational resources.…”
Section: Reproducing Females Have a Fecundity Of 𝑤′mentioning
confidence: 94%
“…Among many considerations, is that once released, it is very difficult to 'recall' the organisms should problems appear (Huang et al 2020). While challenging, these issues are not unsurmountable, as a preliminary trial with the release of engineered mosquitoes has already been reported (Yao et al 2022). As for paratransgenesis, the news is excellent.…”
Section: Prospectsmentioning
confidence: 99%
“…While challenging, these issues are not unsurmountable, as a preliminary trial with the release of engineered mosquitoes has already been reported (Yao et al . 2022). As for paratransgenesis, the news is excellent.…”
Section: Prospectsmentioning
confidence: 99%